Diphtheria with polyneuropathy in a closed community despite receiving recent booster vaccination. Issue 11 (14th October 2005) - Krumina, A; Logina, I; Donaghy, M; Rozentale, B; Kravale, I; Griskevica, A; Viksna, L
Abstract : Introduction and Methods: We report 20 patients aged 18–24 years from Latvia with diphtheritic polyneuropathy. All lived in a closed community and 80% were known to have been fully vaccinated against diphtheria until at least 14 years old. Diphtheria antitoxin had been administered within 3 days of the onset of upper respiratory tract infection in 16 patients and 15 received antibiotics. Results: Neurological symptoms developed after a median of 43 days (range 35–58) compared to only 10 days in previous studies of unvaccinated patients. All showed evidence of mild limb polyneuropathy with electrophysiological evidence of polyneuropathy. Only 30% showed early bulbar abnormalities compared to the usual rate of over 95% in diphtheritic polyneuropathy. However, 45% had later bulbar deterioration coinciding with the limb polyneuropathy. Conclusions: These patients show that an attenuated form of polyneuropathy of later onset, with less prominent early bulbar features, can occur in patients vaccinated against diphtheria according to schedule but living in a closed community in a country where diphtheria remains endemic.